1997
DOI: 10.1002/(sici)1098-237x(199701)81:1<29::aid-sce2>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Concerns and perceptions of beginning secondary science and mathematics teachers

Abstract: This study is an exploratory research project to: (1) identify the concerns that beginning science and mathematics teachers have about being a new teacher; and (2) identify the perceptions that these teachers have about the effectiveness of their preservice program in relation to their concerns. Program, in this context, is defined as pedagogy coursework, content coursework, and undergraduate experiences relevant to teaching. The participants for this study consisted of 11 beginning (less than 2 years experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 12 publications
0
55
0
2
Order By: Relevance
“…Trainees learn to adapt their knowledge, taking learners' needs into account (Lederman et al, op cit;Tuan et al, 1995;Angell et al, 2005). Third, emotional attributes seem to play a part in making a successful transition to -teacher‖ (Adams and Krockover, 1997;de Jong, 2000;Burn, et al, 2007). Good levels of personal selfconfidence and provision of supportive working atmospheres in which collaboration is encouraged benefit novices and experienced teachers alike.…”
Section: Pck In Practice: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trainees learn to adapt their knowledge, taking learners' needs into account (Lederman et al, op cit;Tuan et al, 1995;Angell et al, 2005). Third, emotional attributes seem to play a part in making a successful transition to -teacher‖ (Adams and Krockover, 1997;de Jong, 2000;Burn, et al, 2007). Good levels of personal selfconfidence and provision of supportive working atmospheres in which collaboration is encouraged benefit novices and experienced teachers alike.…”
Section: Pck In Practice: Discussionmentioning
confidence: 99%
“…Baird, Brodie, Bevins and Christol (2007) summarise the extensive lists of competences comprising the professional standards UK and US teachers must meet in order to be -qualified‖. Adams and Krockover (1997) analysed concerns and perceptions held by pre-service science and mathematics teachers. They found that trainees expressed concerns about lack of preparation for teaching, classroom management and organising their time, among others.…”
Section: Pck In Practicementioning
confidence: 99%
“…Classroom management and student discipline are the foremost difficulties that novice science teachers will face as they begin to teach (Adams & Krockover, 1997;Latz, 1992;Lederman & Gess-Newsome, 1991). Beginning to work through these issues is similar for these novice teachers as other novices, especially in student-teaching arrangements (McIntyre et al, 1997;Pilarski, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…When asked what could be done to better prepare them for teaching, graduates in science education often cite among other things the need for more and earlier field experience (Adams & Krockover, 1997). However, questions have existed for some time as to whether more of the same traditional field experience of observation and assistance would help preservice teachers become classroom teachers (McIntyre et al, 1997;Zeichner, 1980).…”
Section: A Situated Learning Model Of Coteaching Was Implemented In Tmentioning
confidence: 99%
“…Tem grandes dificuldades em construir relações de trabalho com o staff escolar. Contempla integralmente as características de um professor novato que viveu durante seu primeiro ano como professor exclusivamente a fase de preocupações consigo mesmo [1], [6], [7], [14], [15].…”
Section: Considerações Finaisunclassified